Task-based learning approach in Java programming - CHIRIAC, Tatiana (Acta et commentationes: Științe ale Educației, 2024)
The task-based learning methodology is examined in this study within the framework of the Java programming language. It emphasizes the idea that students are better able to draw connections between the skills they are learning in a course and real-world issues when they use a task-based approach when studying programming. The purpose of the provided research questions is to clarify various features of the task-based approach found in specialized literature and to demonstrate how it may be used when learning Java programming to construct a task-based program. Choosing activities, integrating training, and establishing explicit objectives are all necessary when creating a task-based program that takes into consideration the needs of the learners.